Carbohydrate inhibitors of cholera toxin - Kumar, Vajinder; Turnbull, W. Bruce (Beilstein Journal of Organic Chemistry, 2018)
Cholera is a diarrheal disease caused by a protein toxin released by Vibrio cholera in the host’s intestine. The toxin enters intestinal epithelial cells after binding to specific carbohydrates on the cell surface. Over recent years, considerable effort has been invested in developing inhibitors of toxin adhesion that mimic the carbohydrate ligand, with particular emphasis on exploiting the multivalency of the toxin to enhance activity. In this review we introduce the structural features of the toxin that have guided the design of diverse inhibitors and summarise recent developments in the field.
Keywords: carbohydrate; cholera; multivalency; toxin

(untitled) - Bryce, J.; Boschi-Pinto, C.; Shibuya, K.; Black, R. E. (Lancet, 2005)

(untitled) - WHO (Wkly. Epidemiol. Rec., 2016)

(untitled) - Ali, M.; Nelson, A. R.; Lopez, A. L.; Sack, D. A. (PLoS Negl. Trop. Dis., 2015)

(untitled) - Merritt, E. A.; Hol, W. G. J. (Curr. Opin. Struct. Biol., 1995)

(untitled) - Fan, E.; Merritt, E. A.; Verlinde, C. L. M. J.; Hol, W. G. J. (Curr. Opin. Struct. Biol., 2000)

Handbook of Natural Toxins - Hol, W. G. J.; Sixma, T. K.; Merritt, E. A. (1995)

(untitled) - van den Akker, F.; Sarfaty, S.; Twiddy, E. M.; Connell, T. D.; Holmes, R. K.; Hol, W. G. J. (Structure, 1996)

(untitled) - Fraser, M. E.; Chernaia, M. M.; Kozlov, Y. V.; James, M. N. G. (Nat. Struct. Mol. Biol., 1994)

(untitled) - Stein, P. E.; Boodhoo, A.; Tyrrell, G. J.; Brunton, J. L.; Read, R. J. (Nature, 1992)

(untitled) - Stein, P. E.; Boodhoo, A.; Armstrong, G. D.; Cockle, S. A.; Klein, M. H.; Read, R. J. (Structure, 1994)

(untitled) - Merritt, E. A.; Sarfaty, S.; van den Akker, F.; L'Hoir, C.; Martial, J. A.; Hol, W. G. J. (Protein Sci., 1994)

(untitled) - Heggelund, J. E.; Burschowsky, D.; Bjørnestad, V. A.; Hodnik, V.; Anderluh, G.; Krengel, U. (PLoS Pathog., 2016)

(untitled) - Merritt, E. A.; Kuhn, P.; Sarfaty, S.; Erbe, J. L.; Holmes, R. K.; Hol, W. G. J. (J. Mol. Biol., 1998)

(untitled) - De Haan, L.; Hirst, T. R. (Mol. Membr. Biol., 2004)

(untitled) - Tomasi, M.; Battistini, A.; Araco, A.; Roda, L. G.; D'Agnolo, G. (Eur. J. Biochem., 1979)

(untitled) - Ampapathi, R. S.; Creath, A. L.; Lou, D. I.; Craft, J. W., Jr; Blanke, S. R.; Legge, G. B. (J. Mol. Biol., 2008)

(untitled) - Zhang, R.-G.; Scott, D. L.; Westbrook, M. L.; Nance, S.; Spangler, B. D.; Shipley, G. G.; Westbrook, E. M. (J. Mol. Biol., 1995)

(untitled) - Zhang, R.-G.; Westbrook, M. L.; Westbrook, E. M.; Scott, D. L.; Otwinowski, Z.; Maulik, P. R.; Reed, R. A.; Shipley, G. G. (J. Mol. Biol., 1995)

(untitled) - Turnbull, W. B.; Precious, B. L.; Homans, S. W. (J. Am. Chem. Soc., 2004)

(untitled) - Johannes, L.; Parton, R. G.; Bassereau, P.; Mayor, S. (Nat. Rev. Mol. Cell Biol., 2015)

(untitled) - Holmner, A.; Lebens, M.; Teneberg, S.; Angstrom, J.; Ökvist, M.; Krengel, U. (Structure, 2004)

(untitled) - Holmner, A.; Askarieh, G.; Oekvist, M.; Krengel, U. (J. Mol. Biol., 2007)

(untitled) - Mandal, P. K.; Branson, T. R.; Hayes, E. D.; Ross, J. F.; Gavín, J. A.; Daranas, A. H.; Turnbull, W. B. (Angew. Chem., Int. Ed., 2012)

(untitled) - Vasile, F.; Reina, J. J.; Potenza, D.; Heggelund, J. E.; Mackenzie, A.; Krengel, U.; Bernardi, A. (Glycobiology, 2014)

(untitled) - St. Hilaire, P. M.; Boyd, M. K.; Toone, E. J. (Biochemistry, 1994)

(untitled) - Holmner, A.; Mackenzie, A.; Krengel, U. (FEBS Lett., 2010)

(untitled) - Wands, A. M.; Fujita, A.; McCombs, J. E.; Cervin, J.; Dedic, B.; Rodriguez, A. C.; Nischan, N.; Bond, M. R.; Mettlen, M.; Trudgian, D. C.; Lemoff, A.; Quiding-Järbrink, M.; et al. (eLife, 2015)

(untitled) - Verlinde, C. L. M. J.; Hol, W. G. J. (Structure, 1994)

(untitled) - Branson, T. R.; Turnbull, W. B. (Chem. Soc. Rev., 2013)

(untitled) - Zuilhof, H. (Acc. Chem. Res., 2016)

(untitled) - Bernardi, A.; Checchia, A.; Brocca, P.; Sonnino, S.; Zuccotto, F. (J. Am. Chem. Soc., 1999)

(untitled) - Bernardi, A.; Arosio, D.; Sonnino, S. (Neurochem. Res., 2002)

(untitled) - Bernardi, A.; Carrettoni, L.; Ciponte, A. G.; Monti, D.; Sonnino, S. (Bioorg. Med. Chem. Lett., 2000)

(untitled) - Cheshev, P.; Morelli, L.; Marchesi, M.; Podlipnik, C.; Bergström, M.; Bernardi, A. (Chem. – Eur. J., 2010)

(untitled) - Heggelund, J. E.; Mackenzie, A.; Martinsen, T.; Heim, J. B.; Cheshev, P.; Bernardi, A.; Krengel, U. (Sci. Rep., 2017)

(untitled) - Merritt, E. A.; Sixma, T. K.; Kalk, K. H.; van Zanten, B. A. M.; Hol, W. G. J. (Mol. Microbiol., 1994)

(untitled) - Merritt, E. A.; Sarfaty, S.; Feil, I. K.; Hol, W. G. (Structure, 1997)

(untitled) - Minke, W. E.; Roach, C.; Hol, W. G. J.; Verlinde, C. L. M. J. (Biochemistry, 1999)

(untitled) - Mitchell, D. D.; Pickens, J. C.; Korotkov, K.; Fan, E.; Hol, W. G. J. (Bioorg. Med. Chem., 2004)

(untitled) - Vrasidas, I.; Kemmink, J.; Liskamp, R. M. J.; Pieters, R. J. (Org. Lett., 2002)

(untitled) - Ramos-Soriano, J.; Niss, U.; Angulo, J.; Angulo, M.; Moreno-Vargas, A. J.; Carmona, A. T.; Ohlson, S.; Robina, I. (Chem. – Eur. J., 2013)

(untitled) - Mammen, M.; Chio, S.-K.; Whitesides, G. M. (Angew. Chem., Int. Ed., 1998)

(untitled) - Badjic, J. D.; Nelson, A.; Cantrill, S. J.; Turnbull, W. B.; Stoddart, J. F. (Acc. Chem. Res., 2005)

(untitled) - Cecioni, S.; Imberty, A.; Vidal, S. (Chem. Rev., 2015)

(untitled) - Pickens, J. C.; Mitchell, D. D.; Liu, J.; Tan, X.; Zhang, Z.; Verlinde, C. L. M. J.; Hol, W. G. J.; Fan, E. (Chem. Biol., 2004)

(untitled) - Arosio, D.; Fontanella, M.; Baldini, L.; Mauri, L.; Bernardi, A.; Casnati, A.; Sansone, F.; Ungaro, R. (J. Am. Chem. Soc., 2005)

(untitled) - Leaver, D. J.; Dawson, R. M.; White, J. M.; Polyzos, A.; Hughes, A. B. (Org. Biomol. Chem., 2011)

(untitled) - Leaver, D. J.; Hughes, A. B.; Dawson, R. M.; Postma, A.; Malic, N.; Polyzos, A. (RSC Adv., 2014)

(untitled) - Liu, J.; Begley, D.; Mitchell, D. D.; Verlinde, C. L. M. J.; Varani, G.; Fan, E. (Chem. Biol. Drug Des., 2008)

(untitled) - Vrasidas, I.; de Mol, N. J.; Liskamp, R. M. J.; Pieters, R. J. (Eur. J. Org. Chem., 2001)

(untitled) - Branderhorst, H. M.; Liskamp, R. M. J.; Visser, G. M.; Pieters, R. J. (Chem. Commun., 2007)

(untitled) - Arosio, D.; Vrasidas, I.; Valentini, P.; Liskamp, R. M. J.; Pieters, R. J.; Bernardi, A. (Org. Biomol. Chem., 2004)

(untitled) - Pukin, A. V.; Branderhorst, H. M.; Sisu, C.; Weijers, C. A. G. M.; Gilbert, M.; Liskamp, R. M. J.; Visser, G. M.; Zuilhof, H.; Pieters, R. J. (ChemBioChem, 2007)

(untitled) - Sisu, C.; Baron, A. J.; Branderhorst, H. M.; Connell, S. D.; Weijers, C. A. G. M.; de, V. R.; Hayes, E. D.; Pukin, A. V.; Gilbert, M.; Pieters, R. J.; Zuilhof, H.; Visser, G. M.; et al. (ChemBioChem, 2009)

(untitled) - Fu, O.; Pukin, A. V.; van Ufford, H. C. Q.; Branson, T. R.; Thies-Weesie, D. M. E.; Turnbull, W. B.; Visser, G. M.; Pieters, R. J. (ChemistryOpen, 2015)

(untitled) - Kumar, V.; Yadav, N.; Kartha, K. P. R. (Carbohydr. Res., 2016)

(untitled) - Fan, E.; Zhang, Z.; Minke, W. E.; Hou, Z.; Verlinde, C. L. M. J.; Hol, W. G. J. (J. Am. Chem. Soc., 2000)

(untitled) - Kitov, P. I.; Sadowska, J. M.; Mulvey, G.; Armstrong, G. D.; Ling, H.; Pannu, N. S.; Read, R. J.; Bundle, D. R. (Nature, 2000)

(untitled) - Merritt, E. A.; Zhang, Z.; Pickens, J. C.; Ahn, M.; Hol, W. G. J.; Fan, E. (J. Am. Chem. Soc., 2002)

(untitled) - Zhang, Z.; Merritt, E. A.; Ahn, M.; Roach, C.; Hou, Z.; Verlinde, C. L. M. J.; Hol, W. G. J.; Fan, E. (J. Am. Chem. Soc., 2002)

(untitled) - Zhang, Z.; Liu, J.; Verlinde, C. L. M. J.; Hol, W. G. J.; Fan, E. (J. Org. Chem., 2004)

(untitled) - Garcia-Hartjes, J.; Bernardi, S.; Weijers, C. A. G. M.; Wennekes, T.; Gilbert, M.; Sansone, F.; Casnati, A.; Zuilhof, H. (Org. Biomol. Chem., 2013)

(untitled) - Mattarella, M.; Garcia-Hartjes, J.; Wennekes, T.; Zuilhof, H.; Siegel, J. S. (Org. Biomol. Chem., 2013)

(untitled) - Zomer-van Ommen, D. D.; Pukin, A. V.; Fu, O.; Quarles van Ufford, L. H. C.; Janssens, H. M.; Beekman, J. M.; Pieters, R. J. (J. Med. Chem., 2016)

(untitled) - Branson, T. R.; McAllister, T. E.; Garcia-Hartjes, J.; Fascione, M. A.; Ross, J. F.; Warriner, S. L.; Wennekes, T.; Zuilhof, H.; Turnbull, W. B. (Angew. Chem., Int. Ed., 2014)

(untitled) - Schengrund, C. L.; Ringler, N. J. (J. Biol. Chem., 1989)

(untitled) - Tran, H.-A.; Kitov, P. I.; Paszkiewicz, E.; Sadowska, J. M.; Bundle, D. R. (Org. Biomol. Chem., 2011)

(untitled) - Mahon, C. S.; Fascione, M. A.; Sakonsinsiri, C.; McAllister, T. E.; Turnbull, W. B.; Fulton, D. A. (Org. Biomol. Chem., 2015)

(untitled) - Polizzotti, B. D.; Kiick, K. L. (Biomacromolecules, 2006)

(untitled) - Richards, S.-J.; Jones, M. W.; Hunaban, M.; Haddleton, D. M.; Gibson, M. I. (Angew. Chem., Int. Ed., 2012)

(untitled) - Mahon, C. S.; McGurk, C. J.; Watson, S. M. D.; Fascione, M. A.; Sakonsinsiri, C.; Turnbull, W. B.; Fulton, D. A. (Angew. Chem., Int. Ed., 2017)

(untitled) - Schofield, C. L.; Field, R. A.; Russell, D. A. (Anal. Chem., 2007)

(untitled) - Poonthiyil, V.; Golovko, V. B.; Fairbanks, A. J. (Org. Biomol. Chem., 2015)

(untitled) - Wands, A. M.; Cervin, J.; Huang, H.; Zhang, Y.; Youn, G.; Brautigam, C. A.; Matson Dzebo, M.; Bjorklund, P.; Wallenius, V.; Bright, D. K.; Bennett, C. S.; Wittung-Stafshede, P.; et al. (ACS Infect. Dis., 2018)